NOWOCZESNOŚĆ W LUSTRZE HISTORII: JACOB BURCKHARDT I FRYDERYK NIETZSCHE WOBEC KULTURY DAWNEJ I WSPÓŁCZESNEJ - Kruszelnicki , Michał (Studia Europaea Gnesnensia, 2018)
The text explores the connections between the ideas of Friedrich Nietzsche and Swiss historian Jacob Burckhardt regarding past and contemporary culture. The focus here is on both thinkers’ highly negative assessment of modernity as an era which does not match the great past times of European culture, especially the noble civilizations of ancient Greece and the Italian Renaissance. The lamentable state of modernity is seen and analyzed in confrontation with those sublime past epochs, with their ethos of individuality, immorality, violent passions and common ambition for greatness. The article ends with a conclusion that although both thinkers were disappointed with times they lived in, it was Nietzsche who pushed his critique of modernity to the extreme, calling for a radical and imminent breach with the failed history and founding a new one, one which would create place only for an elite group of outstanding individuals, while Burckhardt was much more reserved. Although a pessimist too, he kept a desperate faith in the autotelic value of European culture’s spiritual continuum and did not negate its heritage.